Pengembangan Modul Materi Sistem Reproduksi Manusia Berbasis Reading, Questioning And Answering (Rqa) Guna Menunjang Pembelajaran Mandiri dan Keterampilan Berpikir Kritis Siswa - Nesha Anjani Zahrawani; Peni Suharti (Universitas Muhammadiyah Surabaya, 2018)
Abstract : This study aims to produce a product in the form of teaching material of human reproductive system based on RQA in order to support independent learning and critical thinking skills. The research and development of this learning resource were conducted at University of Muhammadiyah Surabaya that limited trial on class XI MIPA 7 SMA Muhammadiyah 2 Surabaya. The method of development of this research was 4-D model by Thiagarajan, et al (1974), covering Define, Design, Develop and Disseminate, but the research was only at Development stage. The results showed that the developed teaching material has scoring criteria,